Истоки - Алданов Марк Александрович (Библиотека "Огонек", 1991)
Экземпляры: ф.1 (1991) / Инвентарный номер: 34182 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 45 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44